“SEARCH FOR NMDAR-A” DALAM DIAGNOSIS PSIKOTIK AUTOIMUN: SERIAL KASUS ENSEFALITIS NMDAR - Hartono Kosim; Michael Surya; Anak Ayu Sri Wahyuni (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
ABSTRACT Anti-NMDAR encephalitis is an autoimmune disorder of the central nervous system that often presents initially with psychiatric symptoms, leading to a high risk of misdiagnosis as functional psychotic disorders. This study aims to evaluate the role of the “Search For NMDAR-A” approach in the early identification of autoimmune psychosis in acute psychotic episodes. The study employed a case series design involving 10 patients collected from November 2023 to June 2024 in the Department of Psychiatry. Evaluation was conducted through clinical psychiatric assessment, longitudinal observation, and cerebrospinal fluid (CSF) examination. Data were analyzed using qualitative descriptive analysis to identify key clinical patterns. The results indicate a dominant combination of symptoms, including sleep disturbances, agitation, and psychosis, with some cases accompanied by catatonia and cognitive impairment. The main finding highlights a consistent pattern of early symptoms accompanied by CSF abnormalities (elevated protein and pleocytosis) as indicators of suspected autoimmune psychosis. The “Search For NMDAR-A” approach shows potential as an initial clinical screening tool prior to definitive antibody testing. Conclusion: This approach is effective in enhancing clinicians’ awareness for the early detection of autoimmune psychosis. The novelty of this study lies in the systematic application of a mnemonic approach within psychiatric clinical practice. ABSTRAK Ensefalitis anti-NMDAR merupakan gangguan autoimun sistem saraf pusat yang sering diawali gejala psikiatri sehingga berisiko tinggi disalahdiagnosis sebagai gangguan psikotik fungsional. Penelitian ini bertujuan mengevaluasi peran pendekatan “Search For NMDAR-A” dalam identifikasi dini psikosis autoimun pada episode psikotik akut. Desain penelitian berupa serial kasus terhadap 10 pasien yang dikumpulkan pada November 2023–Juni 2024 di Departemen Psikiatri. Evaluasi dilakukan melalui asesmen klinis, observasi longitudinal, dan pemeriksaan cairan serebrospinal (CSF). Data dianalisis secara deskriptif kualitatif untuk mengidentifikasi pola klinis utama. Hasil menunjukkan kombinasi gejala dominan berupa gangguan tidur, agitasi, dan psikosis, dengan sebagian kasus disertai katatonia dan gangguan kognitif. Temuan utama adalah konsistensi pola gejala awal yang disertai abnormalitas CSF (peningkatan protein dan pleositosis) sebagai indikator kecurigaan psikosis autoimun. Pendekatan “Search For NMDAR-A” berpotensi sebagai alat skrining awal sebelum uji antibodi definitif. Simpulan: Pendekatan ini efektif meningkatkan kewaspadaan klinisi dalam deteksi dini psikosis autoimun. Kebaruan penelitian terletak pada penerapan sistematis mnemonic dalam praktik psikiatri.